The Trouble with Homogeneous Teams - Mangelsdorf, Martha (MIT Sloan Management Review, 2018)
Many companies are paying increased attention to workplace diversity - issues such as how to increase diversity, how to foster sensitivity to it, and how to manage a diverse workforce. But, according to MIT Sloan School of Management professor Evan Apfelbaum, managers should also factor in issues associated with a related problem: workplace homogeneity. In this interview with MIT Sloan Management Review editorial director Martha E. Mangelsdorf, Apfelbaum explains why diverse groups are sometimes able to reach better decisions than homogenous groups. Recent research, including Apfelbaum's own, has found, for example, that racially homogeneous groups are less rigorous in their decision-making - and make more mistakes - than groups composed of people with racially diverse backgrounds. For example, Apfelbaum notes that in a study that compared trading practices of homogeneous and diverse groups in both Asia and the U.S., members of the racially homogeneous groups showed a greater willingness to pay more than things were worth. What's more, people within such groups were "more likely to copy another person's mistake - presumably assuming that the mistake had some value that they just didn't understand." According to Apfelbaum, this finding suggests "that there is something fundamental about working with similar versus different others that affects individuals' decision-making." Other studies have similarly indicated that diverse groups have fewer blind spots. In diverse groups, Apfelbaum says, people are more likely to "come to an independent assessment of what they think to be the case." In the interview, Apfelbaum observes that "diversity can be both advantageous and complicated in the workplace and in decision-making groups." Many people in social settings gravitate toward people with similar backgrounds, and research has also shown that diverse groups can experience conflict and mistrust. However, conflict isn't necessarily a negative. In one study, for example, different groups were asked to review identical information before reaching their recommendations. The diverse groups tended to consider more perspectives than the homogeneous ones and were more accurate in both their decisions and their assessments of their performance. The homogeneous groups had more confidence in their decisions, but those decisions were actually less accurate.